PENGGUNAAN METODE ANALISA EKOLOGI DAN PENGINDERAAN JAUH UNTUK PEMBANGUNAN SISTEM INFORMASI GEOGRAFIS EKOSISTEM PANTAI - Sukojo, Bangun Muljo (UI Scholars Hub, 2003)
Application of Remote Sensing and Ecology Analysis Method for Geographic Information System of Coastal Ecosystem. With the development that have been done on all Indonesian coastal area, the damaged can be suffered from day to day. The decrease of environmental or ecosystem quality occurred and effected the economic, social and cultural life directly or indirectly. Based on that condition, data or information is needed to look accurately the decrement level and the way to handle it. One method that can be used is a computer based technology which commonly called Geographic Information System (GIS). The technology can gathering, recording, processing and displaying data or information which is obtained directly or indirectly from the field. As the data to be said acceptable with high validity, then before it is being acknowledged, then an ecology analysis and remote sensing technology can be done first.